Numerical Modeling and Simulation of Wind Blown Sand Morphology under Complex Wind-Flow Field - Xamxinur Abdikerem; Lei Wang; Afang Jin; Mamtimin Geni (Journal of Applied Mathematics)
The flow field and the sand flow field constitutive equations are analyzed at first, then the different desert highway numerical models are established by considering the crossroad and by changing the road surface height and air stream flow field, then three kinds of different models with different complex air flow fields are made for simulating the sand ripple formation process by weak coupling of air and sand flow field, and finally the numerical simulations of these models are conducted and the affect process of sand morphology under complex air flow fields are discussed. The results show that under the uniform airflow field, the straight parallel ripple formed and the flared ripple formed in the middle region of the crossroad, and the wavelength of the ripples on the desert highway is bigger than that of the ripples around the road when the road height is higher than that of the sand surface height. Under the nonuniform complex airflow field, the complex curved ripples are formed, and some of the local area, where the whirlwind exits, no ripples are formed.